The historical range of the White-winged Wood-Duck in Indonesia - Green, A J; Crosby, M J (KUKILA, 1992)
Details are provided of historical records of Cairina scutulata in Sumatra and Java. There are confirmed records from seven Sumatran provinces and West and Central Java. These records increase the likelihood that populations survive today in Riau, Bengkulu and elsewhere in Sumatra.